Epidemiological Study of Road Traffic Accidents and Detection of Accident Hot Spot in Golestan Province, Northern Iran - Hassan Khorshah; Maryam Eri; Mohammad Reza Honarvar; Seyed Kamal Mirkarimi; Mahdi Abbasi; Farhad Badiei; Masoumeh Gholami; Mohammad Montazeri (Golestan University Of Medical Sciences, 2018)
Background and objectives: Given the high burden of traffic accidents in Iran, especially in the northern areas, and the importance of identifying the characteristics and geographic distribution of road traffic accidents (RTAs) for policymaking and planning, this study was conducted to investigate the epidemiology of RTAs and determine accident hot spots in the Golestan Province, northern Iran. Methods: This cross-sectional study was carried out on all traffic accidents in the suburban roads of the Golestan Province that were reported to the Emergency Medical Services (EMS 115) and registered in a software-based traffic accidents information management system (called SAMAH in Persian) between March 2009 and 2012. The accidents were assessed in terms of setting, time of accident, demographic characteristics of injured people, and consequences. Data were entered into SPSS (version 16) and then analyzed using independent t-test and chi-square test. The ArcGIS10 software was also used for analyzing spatial data and mapping RTAs. Results: Overall, 10522 incidents were recorded in the system, most of which (36.2%) occurred in March 2010-2011. The frequency of RTAs in summer was almost 2-fold higher than other seasons. In addition, the frequency of RTAs was higher in the Gonbad-e-Kavous County (23.4%) and the Gorgan County (21.4%). Among the 11,415 people injured in RTAs, 9,129 (82.1 %) were male, 80.7% were transferred to hospital, and 5.9% were treated at the accident site. The mean age of injured men (29.9±14.9 years) was significantly lower than that of injured women (33.2±17 years) (P≤0.001). Moreover, 163 individuals (1.4%) died because of the RTAs, and mission was canceled in 1393 cases (12%). The most common RTA injuries were multiple traumas (34.6%), head and face injuries (28.3%), and knee and leg injuries (18.1%). Conclusion: We demonstrated that the rate of RTAs in the Golestan Province is high. Offering training to people, especially to younger people who at higher risk of involvement in RTAs, improving road quality and signage in hot spots, and recruitment of highly-trained EMS personnel might be beneficial for reducing the number and complications of RTAs in the province.